Gluten Quantitation in Cosmetic Products by Enzyme-Linked Immunosorbent Assay. (27th November 2019) - Sharma, Girdhari M; Rallabhandi, Prasad; Williams, Kristina M; Herrmann, Michelle; Sadrieh, Nakissa
Abstract: The "gluten-free" final rule, published by the U.S. Food and Drug Administration (FDA) in 2013, is intended to provide safe food choices for people suffering from celiac disease. This final rule is not applicable for cosmetic products. As a result, analytical methods for gluten estimation in cosmetics are warranted to aid in the determination of the presence of gluten in these products. A survey of 36 cosmetic products was conducted to measure gluten content by three different ELISAs. None of the nine gluten-free–labeled cosmetics included detectable gluten. The gluten content in six cosmetics was 15.2–1453.5 ppm by one competitive ELISA, whereas three cosmetics contained 11.7–572.3 ppm gluten when quantitated with two sandwich ELISAs. Gluten or hydrolyzed wheat protein was found as an ingredient in five cosmetics with detectable gluten levels. A poor recovery of gluten was observed for most of the cosmetics in the foundation/blush/powder category by ELISA kits. This finding warrants a need for improved analytical methods for gluten estimation in cosmetics.